DESIGN AND TESTED A PILOT SCALE OF A GREENHOUSE HYBRID DRYER FOR FERMENTED CASSAVA SLICES - Nurhasanah, Ana; Unadi, Astu; Suherman, Suherman; *, Sularno (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A pilot scale of solar hybrid dryer for fermented cassava chips with wood-burning stoves as additional energy was designed and evaluated. The dimension of dryer was 9.2 m of length, 3.8 m of wide, and 3.54 of high, with capacity 768 kg. The dryer building is made from iron as main frame, Polycarbonate sheet 2 mm of thickness as wall and cement as roof. Tray is made from stainless steel wire mesh with wood and iron as a frame.The test results give 768 kg of fermented cassava chip could be dried in 9 hours, in which 94.3% of initial moisture content becomes 9.4% of final moisture content. The thermal efficiency of dryer is 53.82% with the wood consumption rate is 28.5 kg/h.